MEDIA RELATIONS DI MEDIA MASSA (ANALISIS DESKRIPTIF KUALITATIF TERHADAP KEGIATAN MEDIA RELATIONS TVRI YOGYAKARTA DAN JOGJA TV) - R. Sumantri Raharjo (Profetik: Jurnal Komunikasi, 2015)
Every organization needs to buid it’s image. Media relations is one of the ways to make good image. The activities refer to how organization using media to affect their publics to reach organization goal. Mass media usually be used by corporate to make corporate and product images, but it also needs to build images .This research emphasize on media relations management in media. TVRI Jogja and Jogja TV are choosen to represent public and commercial elect ronic media. It’s aim to know media orientation, technical media relations and their differences.